PENGARUH GOOD CORPORATE GOVERNANCE, PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Olivia Rizqiatul Jannah; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study was to determine the effect of Good Corporate Governance, Profitability and Liquidity on Firm Value in LQ45 Companies listed on the Indonesia Stock Exchange in 2017-2019. The population of this study is LQ45 companies listed on the Indonesia Stock Exchange from 2017 to 2019. The sample used is 11 samples that meet the criteria in the research subject from 2017 to 2019. The analysis method used is multiple regression equation, normality test, classical assumption test., descriptive statistical analysis and hypothesis testing. The results show that Good Corporate Governance, Profitability and Liquidity to Firm Value simultaneously affect the LQ45 Firm Value listed on the Indonesia Stock Exchange in 2017-2019.Keywords : Good Corporate Governance, Profitability, and Liquidity.